Composition and application thereof in concrete
A concrete composition utilizing recycled aggregates with larger particle sizes addresses the lack in existing technologies, enhancing mechanical properties and durability, and reducing environmental impact.
Patent Information
- Application Number
- CN202411255800.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing concrete technologies lack the use of recycled aggregate with larger particle sizes, leading to inefficiencies in resource utilization and environmental impact from waste concrete.
A composition for concrete using recycled block stone, recycled aggregate, artificial sand, silicate cement, fly ash, and water reducer, with recycled aggregate particle sizes ranging from 5 to 60 mm, to enhance mechanical properties and durability.
The composition demonstrates good mechanical properties and durability, such as compressive strength, splitting tensile strength, and frost resistance, making it suitable for large-volume concrete applications while reducing energy consumption and environmental impact.
Smart Images

Figure CN119118594A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of hydraulic materials, and in particular relates to a composition and its application in concrete. Background Art
[0002] During the demolition, construction and reconstruction of buildings such as reservoirs, a large amount of solid waste will be generated. The stacking and landfilling of these solid wastes can easily lead to problems such as land waste and damage to the ecological environment. There are also prominent problems such as difficulty in "excavation and filling balance", large amount of solid waste, and long stacking time. Sometimes the demolished slag needs to be transported to a permanent dumping site.
[0003] Recycled aggregate concrete refers to concrete made by crushing, cleaning, grading solid waste blocks, mixing them with grading in a certain proportion, and partially or completely replacing natural aggregates. It can not only save natural aggregates and protect the ecological environment of the aggregate production area, but also solve the problems of stacking and occupying land and environmental pollution caused by improper treatment of waste concrete. It is a hot topic in academic research today. In the existing technology, the recycled aggregate used in recycled aggregate concrete has a small particle size, and there is a relative lack of research on recycled aggregates with larger particle sizes.
[0004] Therefore, developing a composition and its application in concrete to solve the technical defect of the prior art, which is the lack of concrete containing recycled aggregate with larger particle size, has become an urgent problem to be solved by those skilled in the art. Summary of the invention
[0005] Based on this, it is necessary to provide a composition and its application in concrete to address the technical defect of the existing technology that there is a lack of concrete containing recycled aggregate with larger particle size, and the obtained concrete has good properties.
[0006] The present application provides a composition, the raw materials of which include: recycled block stone, recycled aggregate, artificial sand, silicate cement, fly ash, water reducing agent and water;
[0007] The particle size of the recycled aggregate is 5 to 60 mm.
[0008] In one of the embodiments, the recycled aggregate includes, by mass percentage, 25% to 35% of a first recycled aggregate, 30% to 40% of a second recycled aggregate and 35% to 45% of a third recycled aggregate, the particle size of the first recycled aggregate is 5 to 20 mm, the particle size of the second recycled aggregate is 20 to 40 mm, and the particle size of the third recycled aggregate is 40 to 60 mm.
[0009] In one embodiment, the saturated surface dry apparent density of the recycled aggregate is 2690-2700 kg / m 3The saturated surface dry water absorption rate of the recycled aggregate is 0.22% to 0.37%, the void ratio of the recycled aggregate is 46% to 48%, and the stone powder content of the recycled aggregate is 0.3% to 0.5%.
[0010] In one embodiment, the raw materials of the composition include, by mass: 472-510 parts of recycled block stone, 960-1025 parts of recycled aggregate, 680-709 parts of artificial sand, 104-118 parts of Portland cement, 56-63 parts of fly ash, 1-2 parts of water reducer and 88-95 parts of water.
[0011] In one embodiment, the particle size of the regenerated block stone is 100-250 mm, and the saturated surface dry apparent density of the regenerated block stone is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength of the regenerated block stone is 52.9MPa to 73.1MPa, the softening coefficient of the regenerated block stone is 0.75 to 0.93, and the saturated water absorption rate of the regenerated block stone is 0.44% to 0.52%.
[0012] In one embodiment, the saturated surface dry apparent density of the artificial sand is 2690-2700 kg / m 3 The saturated surface dry water absorption rate of the artificial sand is 1.1% to 1.3%, the stone powder content of the artificial sand is 14.0% to 14.4%, the particle content of the artificial sand is 5.2% to 5.7%, and the fineness modulus of the artificial sand is 2.6 to 2.8.
[0013] In one embodiment, the silicate cement is P·O42.5 cement;
[0014] and / or,
[0015] The fly ash is Class F Grade II fly ash.
[0016] In one embodiment, the water reducer is a slow-setting high-efficiency water reducer, and the water reduction rate of the water reducer is 14% to 15%.
[0017] In one embodiment, the stone embedding rate of the composition is 10% to 20%.
[0018] The present application also provides a use of the composition described in any one of the above items in concrete.
[0019] In summary, the present application provides a composition, the raw materials of which include: recycled stone, recycled aggregate, artificial sand, silicate cement, fly ash, water reducer and water; the particle size of the recycled aggregate is 5 to 60 mm. The present application also provides an application of the above-mentioned composition in concrete. In the technical solution provided by the present application, recycled aggregate with large particle size is used as raw material, which can effectively reduce the processing energy consumption of recycled aggregate; experimental measurements show that the composition has good mechanical properties, such as compressive strength, splitting tensile strength, and durability, such as impermeability grade and frost resistance grade, and can be used as concrete. The composition provided by the present application and its application in concrete solve the technical defect of the prior art that there is a lack of concrete containing recycled aggregate with larger particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0021] Figure 1 This is a scanning electron microscope image of the recycled aggregate used in the composition provided in the examples of the present application;
[0022] Figure 2 This is an EDS spectrum analysis diagram of the recycled aggregate used in the composition provided in the examples of the present application;
[0023] Figure 3 The X-ray diffraction curve of the recycled aggregate used in the composition provided in the embodiment of the present application;
[0024] Figure 4 A cumulative pore volume curve of the recycled aggregate used in the composition provided in the examples of the present application;
[0025] Figure 5 A pore size distribution curve of the recycled aggregate used in the composition provided in the examples of the present application;
[0026] Figure 6 A schematic diagram of a first recycled aggregate in a composition provided in the present application;
[0027] Figure 7 A schematic diagram of a second recycled aggregate in a composition provided in the present application;
[0028] Figure 8 A schematic diagram of a third recycled aggregate in a composition provided in the present application;
[0029] Fig. 9 A schematic diagram of a regenerated block stone in a composition provided in the present application;
[0030] Fig.10 In the technical solution provided in this application, an experimental record diagram of the compressive strength test in Example 6;
[0031] Fig.11 In the technical solution provided in this application, an experimental record diagram of the splitting compressive strength test in Example 6;
[0032] Fig.12 In the technical solution provided in this application, an experimental record diagram of the elastic modulus test in Example 6;
[0033] Fig.13 In the technical solution provided in this application, an experimental record diagram of the anti-seepage grade test in Example 6;
[0034] Fig.14 In the technical solution provided in this application, an experimental record diagram of the antifreeze grade test in Example 6;
[0035] Fig.15 In the technical solution provided in this application, an experimental record diagram of the shrinkage performance test performed in Example 6. DETAILED DESCRIPTION
[0036] The embodiments of the present application provide a composition and its application in concrete, which are used to solve the technical defect of the prior art that there is a lack of concrete containing recycled aggregate with larger particle size.
[0037] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings and examples. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0038] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0039] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0040] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0041] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0042] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.
[0043] In the embodiment of the present application, the recycled aggregate used is a large-size recycled aggregate, and the recycled aggregate is composed of 25% to 35% of a first recycled aggregate, 30% to 40% of a second recycled aggregate and 35% to 45% of a third recycled aggregate; wherein the particle size of the first recycled aggregate is 5 to 20 mm, the particle size of the second recycled aggregate is 20 to 40 mm, and the particle size of the third recycled aggregate is 40 to 60 mm.
[0044] In order to better integrate with other components in the composition and combine with the application requirements of the composition in the later stage of concrete, the saturated surface dry apparent density of the recycled aggregate used in this application is 2690-2700 kg / m 3 The saturated surface dry water absorption rate of the recycled aggregate is 0.22% to 0.37%, the void ratio of the recycled aggregate is 46% to 48%, and the stone powder content of the recycled aggregate is 0.3% to 0.5%.
[0045] Further integration Figures 1 to 5 , Figures 1 to 5 They are respectively the performance index diagrams of the recycled aggregate used in the subsequent examples of this application.
[0046] in, Figure 1 The scanning electron microscope image of the recycled aggregate used is shown in Figure 2. Figure 1 The scanning electron microscope image shows that the microstructure of the recycled aggregate is covered with textures and mineral particles. The main component of these recycled aggregates is calcite (CaCO3), which presents a unique crystal structure and dense arrangement. Since the recycled aggregates come from the demolished dam masonry, these masonry are affected by environmental weathering, dissolution, scouring, etc. during service, resulting in pores and microcracks on their surfaces.
[0047] Figure 2 The EDS spectrum analysis diagram of the recycled aggregate used is shown in Figure 2. Figure 2 From the EDS energy spectrum analysis chart, it can be concluded that: from the EDS energy spectrum analysis chart of recycled aggregate, it can be seen that the main elements of recycled aggregate are composed of Ca, C, and O, the mass ratio of Ca is 31.7%, the mass ratio of C is 13.1%, and the mass ratio of O is 54.8%.
[0048] Figure 3 is the X-ray diffraction curve of the recycled aggregate used. Figure 3 From the X-ray diffraction curve, it can be concluded that the recycled aggregate is mainly composed of CaCO3 with a small amount of SiO2 peak.
[0049] Figure 4 is the cumulative pore volume curve of the recycled aggregate used; Figure 4 The cumulative pore volume curve shows that for recycled aggregate sample 1 (BDG), when the pore size is less than 20nm, the cumulative pore volume fraction reaches 100% and remains unchanged, indicating that the minimum pore size is about 20nm. In the range of 20nm to 60nm, the cumulative pore volume fraction increases significantly, indicating that the structure of BDG dominates in this range. In contrast, the curve of sample 2 (BZG) changes the least between 10nm and 1000nm, indicating that pores smaller than 1000nm are almost non-existent.
[0050] Figure 5is the pore size distribution curve of the recycled aggregate used; Figure 5 The pore size distribution curves show that neither the recycled aggregate sample 1 (BDG) nor the sample 2 (BZG) exhibits gel nanopores (<10nm). The pore size (10-50nm) of BDG accounts for 52.29% of all pore sizes, more than half of the total. There are no mesopores and medium capillary pores (50-100nm) in BZG, and macropores (>5000nm) account for 78.64%. This indicates that BDG has a higher density and smaller pore size.
[0051] In the following embodiments of the present application, the recycled aggregate and recycled block stone used can be found in Figures 6 to 9 .
[0052] Example 1
[0053] This embodiment is a specific composition embodiment of the concrete product 1.
[0054] Concrete product 1 includes: 491kg recycled block stone, 996kg recycled aggregate, 693kg artificial sand, 108kg silicate cement, 57kg fly ash, 1.7kg water reducer and 89kg water; after the above components are mixed evenly, concrete product 1 is obtained, and the stone embedding rate of the obtained concrete product 1 is 10% to 20%.
[0055] In this embodiment, the saturated surface dry apparent density of the regenerated block stone used is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength is 52.9MPa~73.1MPa, the softening coefficient is 0.75~0.93, and the saturated water absorption is 0.44%~0.52%.
[0056] The artificial sand used is 2690~2700kg / m 3 The saturated surface dry water absorption rate is 1.1% to 1.3%, the stone powder content is 14.0% to 14.4%, the particle content is 5.2% to 5.7%, and the fineness modulus is 2.6 to 2.8.
[0057] The silicate cement used is P·O42.5 cement.
[0058] The fly ash used is Class F II fly ash.
[0059] The water reducing agent used is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
[0060] Example 2
[0061] This embodiment is a specific composition embodiment of concrete product 2.
[0062] Concrete product 2 includes: 490kg recycled block stone, 993kg recycled aggregate, 690kg artificial sand, 108kg silicate cement, 57kg fly ash, 1.5kg water reducer and 89kg water; after the above components are mixed evenly, concrete product 2 is obtained, and the stone embedding rate of the obtained concrete product 2 is 10% to 20%.
[0063] In this embodiment, the saturated surface dry apparent density of the regenerated block stone used is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength is 52.9MPa~73.1MPa, the softening coefficient is 0.75~0.93, and the saturated water absorption is 0.44%~0.52%.
[0064] The artificial sand used is 2690~2700kg / m 3 The saturated surface dry water absorption rate is 1.1% to 1.3%, the stone powder content is 14.0% to 14.4%, the particle content is 5.2% to 5.7%, and the fineness modulus is 2.6 to 2.8.
[0065] The silicate cement used is P·O42.5 cement.
[0066] The fly ash used is Class F II fly ash.
[0067] The water reducing agent used is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
[0068] Example 3
[0069] This embodiment is a specific composition embodiment of concrete product 3.
[0070] Concrete product 3 includes: 492kg recycled block stone, 990kg recycled aggregate, 687kg artificial sand, 112kg silicate cement, 59kg fly ash, 1.3kg water reducer and 91kg water; after the above components are mixed evenly, concrete product 3 is obtained, and the stone embedding rate of the obtained concrete product 3 is 10% to 20%.
[0071] In this embodiment, the saturated surface dry apparent density of the regenerated block stone used is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength is 52.9MPa~73.1MPa, the softening coefficient is 0.75~0.93, and the saturated water absorption is 0.44%~0.52%.
[0072] The artificial sand used is 2690~2700kg / m 3The saturated surface dry water absorption rate is 1.1% to 1.3%, the stone powder content is 14.0% to 14.4%, the particle content is 5.2% to 5.7%, and the fineness modulus is 2.6 to 2.8.
[0073] The silicate cement used is P·O42.5 cement.
[0074] The fly ash used is Class F II fly ash.
[0075] The water reducing agent used is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
[0076] Example 4
[0077] This embodiment is a specific composition embodiment of the concrete product 4.
[0078] Concrete product 4 includes: 493kg recycled block stone, 987kg recycled aggregate, 684kg artificial sand, 114kg silicate cement, 60kg fly ash, 1.1kg water reducer and 92kg water; after the above components are mixed evenly, concrete product 4 is obtained, and the stone embedding rate of the obtained concrete product 4 is 10% to 20%.
[0079] In this embodiment, the saturated surface dry apparent density of the regenerated block stone used is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength is 52.9MPa~73.1MPa, the softening coefficient is 0.75~0.93, and the saturated water absorption is 0.44%~0.52%.
[0080] The artificial sand used is 2690~2700kg / m 3 The saturated surface dry water absorption rate is 1.1% to 1.3%, the stone powder content is 14.0% to 14.4%, the particle content is 5.2% to 5.7%, and the fineness modulus is 2.6 to 2.8.
[0081] The silicate cement used is P·O42.5 cement.
[0082] The fly ash used is Class F II fly ash.
[0083] The water reducing agent used is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
[0084] Example 5
[0085] This embodiment is a specific composition embodiment of the concrete product 5.
[0086] Concrete product 5 includes: 492kg recycled block stone, 984kg recycled aggregate, 681kg artificial sand, 681kg silicate cement, 61kg fly ash, 1.0kg water reducer and 93kg water; after the above components are mixed evenly, concrete product 5 is obtained, and the stone embedding rate of the obtained concrete product 5 is 10% to 20%.
[0087] In this embodiment, the saturated surface dry apparent density of the regenerated block stone used is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength is 52.9MPa~73.1MPa, the softening coefficient is 0.75~0.93, and the saturated water absorption is 0.44%~0.52%.
[0088] The artificial sand used is 2690~2700kg / m 3 The saturated surface dry water absorption rate is 1.1% to 1.3%, the stone powder content is 14.0% to 14.4%, the particle content is 5.2% to 5.7%, and the fineness modulus is 2.6 to 2.8.
[0089] The silicate cement used is P·O42.5 cement.
[0090] The fly ash used is Class F II fly ash.
[0091] The water reducing agent used is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
[0092] Comparative Example 1
[0093] The control sample prepared in the comparative example is composed of the following raw materials: 490 parts of natural block stone (burial rate 20%), 993kg of large-size natural aggregate, 690kg of artificial sand, 110kg of cement, 58kg of fly ash, 90kg of water and 1.5kg of water reducing agent.
[0094] Among them, cement is P·O42.5 cement, fly ash is F class II fly ash, and water reducer is slow setting high efficiency water reducer. In the comparative example, only the types of block stone and large-size aggregate are different, and the comparative example is natural block stone and large-size natural aggregate.
[0095] Example 6
[0096] This example is a specific example of performing performance tests on concrete products 1 to 5 and a control product.
[0097] According to the requirements of the "Test Procedure for Hydraulic Concrete" (SL / T 352-2020), concrete products 1 to 5 and the reference product were made into specimens of corresponding sizes, and their compressive strength, splitting tensile strength, elastic modulus, shrinkage test, impermeability test and frost resistance test were tested respectively. Figure 10-Figure 15 They are the records of the above experimental measurements respectively. The results are shown in Table 1.
[0098] Table 1
[0099]
[0100] From Table 1, it can be concluded that the compressive strength, splitting compressive strength and elastic modulus of concrete products 1 to 5 are slightly lower than those of the control product, but all meet C 90 20 (after 90 days of standard curing, the compressive strength of concrete cube reaches 20MPa) strength design requirement.
[0101] The 90d (90d refers to the standard curing period of 90 days) shrinkage rates of concrete products 1 to 5 are slightly larger, and the impermeability grades all meet the design requirements of W6 (the impermeability grade refers to the maximum water pressure that concrete can withstand without water seepage. W6 means that concrete can withstand a maximum water pressure of 0.6MPa without water seepage). The frost resistance grades all meet the design requirements of F50 (the frost resistance grade is an indicator of the frost resistance of concrete. It is defined by the number of repeated freeze-thaw cycles that the concrete specimen can withstand under specific conditions. F50 means that after 50 freeze-thaw cycles, the relative dynamic elastic modulus of the concrete is greater than 60% and the mass loss rate is less than 5%, indicating that the frost resistance grade of the concrete is F50).
[0102] It can be concluded that the mechanical and durability properties of the product produced by the technical solution provided in this application are very close to those of large-volume concrete with large-particle natural aggregates, and all indicators meet the conventional large-volume concrete design requirements of C9020W6F50, and can be widely used as a backup raw material for large-volume concrete in water conservancy projects.
[0103] It can be concluded from the above embodiments that the technical solution provided by this application has the following advantages:
[0104] 1. In this application, large-size recycled aggregate is used to produce concrete, which can not only save natural aggregate and protect the ecological environment of the aggregate production area, but also solve the problem of resource waste and environmental pollution caused by landfill and stacking of construction waste, and provide strong technical support for the resource utilization of solid waste, which is in line with the concept of green environmental protection and promotes concrete manufacturing to develop in a more green, low-carbon and sustainable direction.
[0105] 2. In this application, large-size recycled aggregate is prepared from solid waste as raw material, which can reduce energy consumption by about 50% compared with the processing energy consumption of small-size aggregate, and significantly reduce the preparation cost of aggregate.
[0106] 3. In this application, when large-size recycled aggregate is used to prepare concrete, less cement is required, which can save about 30% of cement consumption, reduce the thermal insulation temperature rise of concrete by 20% to 26%, and save about 50% of the cost of concrete anti-cracking measures. It greatly simplifies the temperature control process and construction technology of concrete, reduces the input of materials, labor and equipment, improves construction efficiency, significantly reduces construction costs, and has outstanding economic benefits.
[0107] 4. In this application, concrete containing large-size recycled aggregate belongs to the category of mass concrete, and has high use value and application prospects in mass concrete structures of water conservancy project dams, reinforced concrete structures with low reinforcement ratios, etc.
[0108] In summary, the present application provides a composition, the raw materials of which include: recycled stone, recycled aggregate, artificial sand, silicate cement, fly ash, water reducer and water; the particle size of the recycled aggregate is 5 to 60 mm. The present application also provides an application of the above-mentioned composition in concrete. In the technical solution provided by the present application, recycled aggregate with large particle size is used as raw material, which can effectively reduce the processing energy consumption of recycled aggregate; experimental measurements show that the composition has good mechanical properties, such as compressive strength, splitting tensile strength, and durability, such as impermeability grade and frost resistance grade, and can be used as concrete. The composition provided by the present application and its application in concrete solve the technical defect of the prior art that there is a lack of concrete containing recycled aggregate with larger particle size.
[0109] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. At the same time, other implementation methods can be derived from the above-mentioned embodiments, so that structural and logical replacements and changes can be made without departing from the scope of this disclosure.
[0110] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A composition, characterized in that The raw materials of the composition include: recycled block stone, recycled aggregate, artificial sand, silicate cement, fly ash, water reducing agent and water; The particle size of the recycled aggregate is 5 to 60 mm.
2. The composition according to claim 1, characterized in that In terms of mass percentage, the recycled aggregate includes: 25% to 35% of a first recycled aggregate, 30% to 40% of a second recycled aggregate and 35% to 45% of a third recycled aggregate. The particle size of the first recycled aggregate is 5 to 20 mm, the particle size of the second recycled aggregate is 20 to 40 mm, and the particle size of the third recycled aggregate is 40 to 60 mm.
3. The composition according to claim 1 or 2, characterized in that The saturated surface dry apparent density of the recycled aggregate is 2690-2700 kg / m 3 The saturated surface dry water absorption rate of the recycled aggregate is 0.22% to 0.37%, the void ratio of the recycled aggregate is 46% to 48%, and the stone powder content of the recycled aggregate is 0.3% to 0.5%.
4. The composition according to any one of claims 1 to 3, characterized in that The raw materials of the composition include, by weight: 472-510 parts of recycled block stone, 960-1025 parts of recycled aggregate, 680-709 parts of artificial sand, 104-118 parts of Portland cement, 56-63 parts of fly ash, 1-2 parts of water reducer and 88-95 parts of water.
5. The composition according to any one of claims 1 to 4, characterized in that The particle size of the regenerated block stone is 100-250 mm, and the saturated surface dry apparent density of the regenerated block stone is 2680 kg / m 3 ~2690kg / m 3 The saturated uniaxial compressive strength of the regenerated block stone is 52.9MPa to 73.1MPa, the softening coefficient of the regenerated block stone is 0.75 to 0.93, and the saturated water absorption rate of the regenerated block stone is 0.44% to 0.52%.
6. The composition according to any one of claims 1 to 4, characterized in that The saturated surface dry apparent density of the artificial sand is 2690-2700 kg / m 3 The saturated surface dry water absorption rate of the artificial sand is 1.1% to 1.3%, the stone powder content of the artificial sand is 14.0% to 14.4%, the particle content of the artificial sand is 5.2% to 5.7%, and the fineness modulus of the artificial sand is 2.6 to 2.
8.
7. The composition according to any one of claims 1 to 4, characterized in that The silicate cement is P·O42.5 cement; and / or, The fly ash is Class F Grade II fly ash.
8. The composition according to any one of claims 1 to 4, characterized in that The water reducing agent is a slow-setting high-efficiency water reducing agent, and the water reducing rate of the water reducing agent is 14% to 15%.
9. The composition according to any one of claims 1 to 4, characterized in that The stone embedding rate of the composition is 10% to 20%.
10. Use of the composition according to any one of claims 1 to 9 in concrete.
Citation Information
Patent Citations
Recycled large aggregate concrete capable of being mixed and poured and preparation method thereof
CN111499297A
Construction method for improving anti-cracking and anti-seepage performance of stone-buried concrete dam
CN114991075A
Recycled rock-fill concrete
CN115010443A
